Pengaruh Gender Dan Muatan Etika Dalam Pengajaran Akuntansi Keuangan Pada Persepsi Etika Mahasiswa - Farly Frangky Prang; Sparta Sparta (Universitas Multimedia Nusantara, 2015)
The objective of this research was to examine the effect of intellectual capital toward firm’s performance. In this research, intellectual capital was measured by VAIC™. The samples in this study were banking companies that were listed in Indonesia Stock Exchange consecutively from 2012 till 2013. The sample in this study determined based on purposive sampling method. Data used in this study is a secondary data. Data used in this study was analyzed by using Partial Least Squares. In total, there were 26 banking companies that fulfill the requirements set by the researcher. This study tests three elements of VAIC™ and firm’s performance.The results of this study were intellectual capital (VAIC™) has effect on firm’s performance; intellectual capital (VAIC™) has effect on future firm’s performance; and the rate of growth intellectual capital (ROGIC) has no effect on future firm’s performance. Key words: Firm’s Performance, Intellectual Capital, Partial Least Squares, VAICTM